2020
DOI: 10.1259/dmfr.20190272
|View full text |Cite
|
Sign up to set email alerts
|

CT-like MRI using the zero-TE technique for osseous changes of the TMJ

Abstract: Objective: This study was conducted to assess the clinical usability of the zero-echo time (ZTE) technique of MRI for evaluating bone changes of the temporomandibular joint (TMJ) in comparison with CBCT. Methods: Twenty patients with TMJ disorder who underwent both CBCT and MRI were randomly selected. CBCT images were obtained with an Alphard 3030 device (Asahi Roentgen Ind., Co. Ltd, Kyoto, Japan). MRIs were obtained using a 3.0 T scanner (Pioneer; GE Healthcare, Waukesha, WI, USA) and a 21-channel head coil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 18 publications
1
39
0
3
Order By: Relevance
“…MRI is currently considered the gold standard in the diagnosis of morphology and position of the temporomandibular joint disc [27,28]. Moreover, recent research by Lee et al [29] stated that zero-echo time (ZTE) technique of MRI might be clinically useful for assessment of bony changes in temporomandibular joint (TMJ) disorders. The authors used a 3.0 T scanner with a 21-channel head coil.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…MRI is currently considered the gold standard in the diagnosis of morphology and position of the temporomandibular joint disc [27,28]. Moreover, recent research by Lee et al [29] stated that zero-echo time (ZTE) technique of MRI might be clinically useful for assessment of bony changes in temporomandibular joint (TMJ) disorders. The authors used a 3.0 T scanner with a 21-channel head coil.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…MRI is known to be useful for evaluating discs and soft tissues (7). Conventional MRI has limitations in obtaining optimal bone images, and a study using the zero-TE sequence to compensate for these limitations have been reported (8). MRI is absolutely contraindicated in patients with ferromagnetic vascular clips and pacemakers, and imaging may be difficult if the patient experiences claustrophobia, which occurs in 1-15% of patients undergoing MRI (9).…”
Section: Introductionmentioning
confidence: 99%
“…More important, quantitative and functional evaluation of multiple biochemical properties of TMJ structures has become feasible, and has been preliminarily investigated by applying various MRI sequences and sophisticated postprocessing algorithms, 15–17 thereby providing a better understanding of TMJ structures and a better comprehension of its disorders. Moreover, using the novel technique of zero echo time (ZTE), the comparable diagnostic value of osseous abnormalities in TMJ has also been achieved in MRI 18 …”
mentioning
confidence: 99%